As dualidades na filosofia de Bergson - Ribeiro, Felipe (2018)
This dissertation deals with some aspects considered to be dual in Bergson's work, such as Internal / External, Movement / Rest, Freedom / Determinism, Matter / Spirit and Open Morality / Closed Morality.